2022
DOI: 10.3389/fpls.2022.961872
|View full text |Cite
|
Sign up to set email alerts
|

Plant hormones and neurotransmitter interactions mediate antioxidant defenses under induced oxidative stress in plants

Abstract: Due to global climate change, abiotic stresses are affecting plant growth, productivity, and the quality of cultivated crops. Stressful conditions disrupt physiological activities and suppress defensive mechanisms, resulting in stress-sensitive plants. Consequently, plants implement various endogenous strategies, including plant hormone biosynthesis (e.g., abscisic acid, jasmonic acid, salicylic acid, brassinosteroids, indole-3-acetic acid, cytokinins, ethylene, gibberellic acid, and strigolactones) to withsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 176 publications
(103 citation statements)
references
References 312 publications
1
74
0
Order By: Relevance
“…Plants frequently accumulate free proline and soluble sugar to alleviate osmotic stress, which is involved in maintaining membrane integrity with optimal water potential ( Quilambo, 2004 ). Sugar is also involved in the regulation of photosynthesis, stress-responsive genes, antioxidant system, and alleviation of abiotic stress ( Sami et al., 2016 ; Raza et al., 2022a ). However, the higher concentration of proline and soluble in this study provided more support to ZM for coping salt-induced osmotic stress than XJD.…”
Section: Discussionmentioning
confidence: 99%
“…Plants frequently accumulate free proline and soluble sugar to alleviate osmotic stress, which is involved in maintaining membrane integrity with optimal water potential ( Quilambo, 2004 ). Sugar is also involved in the regulation of photosynthesis, stress-responsive genes, antioxidant system, and alleviation of abiotic stress ( Sami et al., 2016 ; Raza et al., 2022a ). However, the higher concentration of proline and soluble in this study provided more support to ZM for coping salt-induced osmotic stress than XJD.…”
Section: Discussionmentioning
confidence: 99%
“…When plants are subjected to stress, a large number of osmotic adjustment substances are accumulated to maintain cell osmotic potential. 15 , 28 For instance, Li, Zeng 21 found that the soluble sugar, soluble protein, and proline contents were increased by MEL in rapeseed seedlings under drought conditions. 21 Melatonin significantly increased the content of soluble protein, sugar, and proline and the SOD and POD activity of wheat seedlings at low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Phytohormones coordinate all aspects of plant growth and development, as well as stress responses ( Shan et al., 2012 ). Plant hormones interact with five key plant neurotransmitters, including serotonin, melatonin, dopamine, acetylcholine and γ-aminobutyric acid, and participate in many physiological processes such as photosynthesis, oxidative stress and osmotic regulation ( Raza et al., 2022b ). Two groups of phytohormones, auxins and cytokinins, have been clearly demonstrated as the main regulators of plant development ( Benjamins and Scheres, 2008 ; Werner and Schmülling, 2009 ; Schaller et al., 2015 ) and stress responses ( Hare et al., 1997 ; Blakeslee et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%